2022
DOI: 10.1037/rep0000470
|View full text |Cite
|
Sign up to set email alerts
|

African American Alzheimer’s Caregiver Training and Support Project 2 (ACTS2) pilot study: Outcomes analysis.

Abstract: Purpose/Objective: The purpose of this study was to conduct an initial evaluation of the quantitative and qualitative outcomes of the African American Alzheimer's Caregiver Training and Support Project 2 (ACTS2). Quantitative objectives focused on assessing changes in caregiver depression and health status, as well as the severity of caregiving and self-care problems from pre-to postintervention. Secondary quantitative analyses examined posttreatment changes in social support and caregiver burden. Qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Indeed, potential differences in health beliefs about self-care may require culturally relevant tailoring to enhance intervention efficacy. 49,50 With these caveats in mind, this randomized controlled pilot study showed preliminary evidence that bvFTD caregivers benefited from virtual health coaching. We also observed that the behavior of care recipients of caregivers who received health coaching improved over time.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Indeed, potential differences in health beliefs about self-care may require culturally relevant tailoring to enhance intervention efficacy. 49,50 With these caveats in mind, this randomized controlled pilot study showed preliminary evidence that bvFTD caregivers benefited from virtual health coaching. We also observed that the behavior of care recipients of caregivers who received health coaching improved over time.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, potential differences in health beliefs about self‐care may require culturally relevant tailoring to enhance intervention efficacy. 49 , 50 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, not all OSGs consider the gender, racial, cultural, or faith-based background of participants, which may impact the efficacy of the support [ 74 ]. Motivations for caregiving can be influenced by cultural underpinnings, such as filial piety, familism, and repayment and reciprocity [ 75 ], and support services should be sensitive of specific cultural values [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a general issue of bias in research toward White caregiver groups in the United States [ 74 ]. Although a strength of this review is that it captured studies from different countries and cultures, the ethnic make-up of samples from outside the United States was not always recorded.…”
Section: Discussionmentioning
confidence: 99%